Ficus deltoidea ethanolic leaves extract improves hormonal balance among letrozole induced polycystic ovarian syndrome (PCOS) rats - Nur Ajeerah Suhaimi; Nooraain Hashim; Nurdiana Samsulrizal (Penerbit Universiti Kebangsaan Malaysia, 2017)
The global prevalence of polycystic ovarian syndrome (PCOS) has reached epidemic proportion contributing to female infertility. The two phenotypes of PCOS, hyperandrogemia and hyperinsulinemia have gained much attention even the exact etiology of the syndrome remained unclear. In the present study, Ficus deltoidea was evaluated to elucidate the effects of its ethanolic leaves extract on several PCOS key hormones of female Sprague Dawley rats induced with letrozole (1.0 mg/kg bwt.). Experimental animals were divided into six groups (A, B, C, D, E and F). Five groups (B, C, D, E and F) were induced into PCOS using 1.0 mg/kg letrozole and the sixth group, Group A was the non PCOS normal control (NC). Groups of PCOS induced rats were treated with: saline (B, PC), 10 mg/kg bwt. clomiphene citrate (C, PCC), and Groups D, E and F were treated with 25, 125 and 250 mg/kg bwt. of F. deltoidea ethanolic leaves extracts, respectively, (PFD25, PFD125 and PFD250). Absence of estrus phase from rat reproductive cycle throughout the induction period (21 days) with significantly higher (p<0.05) testosterone level than NC rats were observed among PCOS induced groups manifested PCOS development in the studied animal model. Hormonal profiling at the end of treatment period revealed significant reduction (p<0.05) in testosterone, FSH and LH levels, but significant increase (p<0.05) in both progesterone and estrogen levels in extract treated groups compared with PC group. Meanwhile, insulin level was significantly reduced (p<0.05) with value 0.265±0.046 ng/mL in PFD125 group compared with that of PC rats (0.801±0.025 ng/mL) suggesting improved insulin sensitivity in the extract treated PCOS rats. In summary, these results indicate the potential use of F. deltoidea leaves in ameliorating PCOS associated risks, since it is capable of alleviating excess androgen and enhancing insulin sensitivity in letrozole-induced PCOS rats.